New approach to territorial planning in ukraine taking into account processe of decentralizationand austrias experience - Dorosh, A. (Land Management, Cadastre and Land Monitoring, 2017)
Scientific publications, legislation on spatial planning in Ukraine and spatial planning in Austria are analysed.Ukrainian spatial planning system is divided into urban planning and land management planning.According to the Law of Ukraine "On regulation of urban development" urban planning documentation is developed for: the entire territory of Ukraine, the region (a part of Ukraine’s territory) and as well for settlements and their parts.According to the Law of Ukraine "On Land Management" most land management documents are developed on the local level.Only two types of land management documentation are developedon the regional level, namely: a) land management schemes and feasibility studies of land use and land protection of administrative units; b) land management projects for the establishment (changing) of the boundaries of administrative units. Such projects as land management projects on ordering the territory for urban needs and land management projects on ordering the residential areas are developed on the local level.Other land management documentation is developed for a particular land parcel (setting boundaries, separation, change of purpose and so on.), or has a narrow specialization (area organization of agricultural land parcels, or providing the environmental and economic assessment of crop rotation). It’s found that almost all planning tolls belong to urban planning.Austrian spatial planning has three levels with clear division of competences in all areas. Planning occurs at the level of the federal government, the federal land and the community. Also nominal spatial planning and professional planning in various fields, which has a significant impact on the environment is defined. Analysis of planning competencies at various levels shows that the lower the level of planning, the higher competence in nominal spatial planning and the lower in professional planning.At first a concept of local development which contains the ideas and goals of development without a clear spatial reference (so-called vision of future) is developed. Based on this concept a plan for targeted purposes is developed.It clearly defines the boundaries of land parcelswith appropriate purpose. The next step is to make a plan of development for areas that are designated for residential, public or industrial building.This plan put restrictions and requirements for newbuildings,namely for their superficiality, compactness, density and possible use. Like the planning hierarchy, there is also a hierarchy of planning and cartographic materials of all planning levels.During the process of comparing the approaches to spatial planning in Austria and spatial planning in Ukraine was found that the spatial planning system of Ukraine requires conceptual changes.Therefore, it is proposed to upgrade the system of spatial planning to a hierarchical system, to refuse from separation of urbanplanning and spatial planning and land management and to update the tolls of this process at the local level (at the level of local communities).It is proposed instead of the Master Plan of settlement, which in the present conditions of land relations reforming is not able to ensure the effective planning processes to implement a plan for target purposes and restrictions for the entire community and to develop on this basis detailed plans for areas designated for built up. This approach will provide a unified system of spatial planning for the successful development of both urban and rural communities.Keywords: spatial planning, municipalities, planning levels, local development.